Pengaruh Insektisida Organoklorin Endosulfan Terhadap Daya Tetas Telur Ikan Nila (Oreochromis Niloticus) - Anggia Cahyati Putri (UNIVERSITAS NEGERI PADANG, 2017)
Uncontrolled usage of pesticides can contaminate the environment such as water, soil, and air. This occurs because the residue of pesticides. One of them, organochlorine insecticides have widely used by farmers because it is persistent. This study aims to look at the effects caused by organochlorine insecticide endosulfan on hatchability of eggs tilapia (Oreochromis niloticus). This research was conducted CRD with 6 treatments and 4 replications. Concentrations of organochlorine endosulfan in treatment are determined based on the LC50. The treatment use organochlorine endosulfan at concentrations of 0.00395%, 0.00400%, 0.00405%, 0.00410% and 0.00415%. Then they observed for 4 days (96 hours). The data obtained and analyzed by ANOVA and followed by DNMRT (Duncan's New Multiple Range Test). The result showed organochlorine insecticide endosulfan significantly (p<0,05) affect hatchability of eggs tilapia (Oreochromis niloticus), but no significant effect on larval abnormalities. Hatchability of eggs tilapia (Oreochromis niloticus) and the highest larval abnormalities are found in P1 which is a control treatment. While the hatchability of eggs and larvae abnormalities lowest for the P6 treatment with concentrations of endosulfan treatment 0.00415%.Keywords: endosulfan, Tilapia (Oreochromis niloticus), hatchability